Persian poetry at the Indian frontier Masʿûd Saʿd Salmân of Lahore - Sharma, Sunil (Permanent Black monographs : The "OPUS 1" series, 2000)
Study on the poetry of Persian poet Masʻûd Saʻd Salmân, 1046 or 7-1121 or 2.